Answer:
B) f(x) = 3x² - 2x + 5
Step-by-step explanation:
To find the correct quadratic function that represents the table, you must substitute [x] into the quadratic function.
A) f(x) = 3x² + 2x - 5
B) f(x) = 3x² - 2x + 5
C) f(x) = 2x² + 3x - 5
D) f(x) = 2x² - 2x + 5
A. 3(-2)² + 2(-2) - 5 =
3(4) - 4 - 5
12 - 4 - 5
12 - 9
= 3
B. 3(-2)² - 2(-2) + 5 =
3(4) + 4 + 5
12 + 9
= 21
C. 2(-2)² + 3(-2) -5 =
2(4) - 6 - 5
8 - 11
= - 3
D. 2(-2)² + 2(-2) + 5 =
2(4) - 4 + 5
8 - 4 + 5
8 + 1
= 9
Your correct answer is: B
Since this is a compound interest problem, you have to take note that the amount Catherine will get per year is not the same. It will increase per year since it is compounded. So first, we get the amount after one year. This will be 7000 x 0.04 which is 280 plus 7280. In the second year, she will get 7571 (7280 x 0.04 + 7280). In the third year, she will get 7874 (7571 x 0.04 + 7571). In the fourth year, she will get 8189 (7874 x 0.04 + 7874). And finally in the fifth year, she will get 8517 (8189 x 0.04 +8189). So after five years, she has 8517
Answer:
- a) 2x -y = -5; A=2, B=-1, C=-5
- b) y = 2x +5
Step-by-step explanation:
a) Standard Form is ...
Ax + By = C
where A > 0 and A, B, C are mutually prime.
To get that form, we can add 2x-5 to both sides of the equation:
(2x -5) -2x = (2x -5) -y +5
-5 = 2x -y
Then we can swap sides of the equal sign:
2x -y = -5 . . . . . . standard form
Matching this to the generic standard form equation, we find ...
A = 2
B = -1
C = -5
__
b) We can solve for y by adding 2x+y to both sides of the equation:
(2x +y) -2x = (2x +y) -y +5
y = 2x +5 . . . . . . slope-intercept form